Pengaruh Model Pembelajaran Contextual Teaching and Learning (CTL) terhadap Hasil Belajar Siswa pada Tema 8 Subtema 1 Pembelajaran 4 di Kelas V UPTD SD N 122332 Jl. Jenderal Sudirman - Juli Yanti Situmorang; Lisbet. N Sihombing; Desi Sijabat (Journal on Education, 2023)
This exploration aims to determine the effect of using the model Contextual Teaching and Learning on student learning outcomes theme 8 sub-theme 1 learning 4 class V UPTD SD Negeri 122332Jl. General Sudirman. This exploration was carried out at UPTD SD Negeri 122332 Jl. Jenderal Sudirman, in May 2023. The exploration used was quantitative exploration using a Quasi Experimental Design of the Nonequivalent Control Group Design type with 47 students in class VA and 5 B as samples. The variables in this exploration are the Contextual Teaching and Learning (X) model and learning outcomes (Y). Methods of data collection by using tests. Data analysis techniques used normality tests, homogeneity tests, hypothesis tests. Based on the results of the exploration that has been carried out, the Contextual Teching and Learning model test data with a sample of 47 students, then the sum of the experimental class pretest scores with an average value of 47.83 . Posttest experimental class with an average value of 86.61. Pretest control class with an average value of 26.88. Posttest control class with an average value of 41.46.